'Research clinics': online journal clubs between south and north for student mentoring. Issue 1 (1st December 2016) - Atkins, Salla; Varshney, Dinansha; Meragia, Elnta; Zwarenstein, Merrick; Diwan, Vishal
Abstract : Background: Capacity development in health research is high on the agenda of many low- and middle-income countries. Objective: The ARCADE projects, funded by the EU, have been working in Africa and Asia since 2011 in order to build postgraduate students' health research capacity. In this short communication, we describe one initiative in these projects, that of research clinics – online journal clubs connecting southern and northern students and experts. Design: We describe the implementation of these research clinics together with student and participant experiences. Results: From 2012 to 2015, a total of seven journal clubs were presented by students and junior researchers on topics related to global health. Sessions were connected through web conferencing, connecting experts and students from different countries. Conclusions: The research clinics succeeded in engaging young researchers across the globe and connecting them with global experts. The contacts and suggestions made were appreciated by students. This format has potential to contribute toward research capacity building in low- and middle-income countries.